Antibacterial starch-based split film fiber for degradable fishing net as well as preparation method and application of antibacterial starch-based split film fiber
Through the composite modification of montmorillonite-guanidine salt and the optimization of starch-based material ratio, antibacterial fishing net materials with good mechanical properties, degradability and antibacterial properties were prepared, which solved the problems of insufficient antibacterial properties and poor mechanical properties of existing fishing net materials, and reduced marine environmental pollution.
Patent Information
- Application Number
- CN202510485070.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-06-27
AI Technical Summary
The existing fishing net materials have insufficient antibacterial properties, poor mechanical properties, and discarded fishing gear has caused pollution to the marine ecological environment.
The degradable antibacterial starch-based cracked film fibers modified with montmorillonite-guanidine salt composite are used to improve the compatibility and mechanical properties of the material through material combination and nanomaterial addition, and antibacterial effect is achieved through the addition of guanidine salt polymer.
The prepared fishing net materials have good mechanical properties, degradability and antibacterial properties, which reduce pollution to the marine environment and improve market competitiveness.
Smart Images

Figure CN120210990A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fishing net materials, and particularly relates to an antibacterial starch-based split film fiber for degradable fishing nets, a preparation method thereof, and an application thereof. Background Art
[0002] The breeding and fishing of aquatic organisms are the pillar industries of the current fishery development, and fishing gear is an essential item in the aquaculture industry. With the development of China's fishery, the usage of fishing gear has gradually increased, and discarded fishing gear will cause irreparable harm to the ecological environment and marine organisms. For example, discarded fishing nets and fishing lines are prone to entangling marine organisms or being accidentally ingested by marine organisms, leading to their death. Discarded fishing gear left in the ocean for a long time will also pollute the marine ecological environment. In addition, it will also have an adverse impact on the marine economy. For example, it will lead to a reduction in fishery resources and an increase in the cost of dealing with discarded fishing gear.
[0003] Based on the national ecological environmental protection strategy vigorously advocated, the development of degradable materials has well responded to the national call. Starch, as a polymer raw material with a wide source, low cost, and green environmental protection and pollution-free in nature, has received great attention from researchers. However, the disadvantages such as poor mechanical properties of starch products limit its application. By adding other polymer materials and compounding them, its disadvantages can be effectively improved. In addition, due to the strong intermolecular forces, high hydrophilicity, and high crystallinity of starch, there are problems in processing. Poly(butylene adipate-co-terephthalate) (PBAT) is a polyester polymer with excellent mechanical properties. It is worth noting that PBAT also has the property of being degradable. In the previous research, it was found that how to improve the compatibility of the two is the problem to be solved at present. In addition, in terms of performance optimization, the mechanical properties and degradation properties of the substrate can be effectively changed by adding nanomaterials, and montmorillonite (MMT) is a layered nanomaterial with low cost and no pollution. Therefore, it is a good choice to use it as an additive. Summary of the Invention
[0004] To solve the above technical problems, the present invention provides an antibacterial starch-based split film fiber for degradable fishing nets, a preparation method thereof, and an application thereof. Compared with the traditional silk processing, the preparation of the split film fiber of the present invention has the advantages of simple equipment, high production efficiency, and low cost. The prepared split film fiber can be used for twisting and then weaving fishing nets and other utensils, so that the fishing net has good mechanical properties while taking into account degradability and antibacterial properties, and this material can have good market competitiveness in the fishing market.
[0005] To achieve the above object, the present invention provides a preparation method of an antibacterial starch-based split film fiber for degradable fishing nets, comprising the following steps:
[0006] (1) Mixing a layered nanomaterial with a guanidine salt polymer to obtain a primary mixture;
[0007] (2) Starch drying, the dried starch, glycerol, epoxy vegetable oil and the premix obtained in step (1) are mixed, and then polybutylene adipate / terephthalate is added to obtain a premix;
[0008] (3) The premix obtained in step (2) is heated and plasticized, and pelletized to obtain pellets;
[0009] (4) The pellets obtained in step (3) are blown into a film, and the film is divided to obtain split film fibers.
[0010] Preferably, the layered nanomaterial in step (1) is montmorillonite; the guanidine salt polymer in step (1) is polyhexamethylene guanidine hydrochloride (PHMG).
[0011] Preferably, the drying temperature in step (2) is 60 - 80 °C, and the drying time is 5 - 7 h.
[0012] Preferably, the mass ratio of the dried starch, glycerol and epoxy vegetable oil in step (2) is 10:3:0.5; the mass of the layered nanomaterial in step (1) accounts for 0.3% of the mass of the premix; the mass of the guanidine salt polymer in step (1) accounts for 1% of the mass of the premix; the mass of the polybutylene adipate / terephthalate in step (2) accounts for 30% - 50% of the mass of the premix.
[0013] Preferably, the starch in step (2) is corn starch; the epoxy vegetable oil in step (2) is one of epoxy soybean oil, castor oil and palm oil.
[0014] Preferably, the heating and plasticization in step (3) is carried out in a twin-screw extruder, and the working temperature of the twin-screw extruder is set as 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C, and the screw speed of the twin-screw extruder is 100 - 140 rpm.
[0015] Preferably, the pelletizing speed in step (3) is 180 rpm.
[0016] Preferably, the film blowing in step (4) is carried out in a film blowing machine, and the working temperature of the film blowing machine is set as 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C, the rotation speed of the film blowing machine is 60 - 100 rpm, the traction speed of the film blowing machine is 3; the width of the division treatment in step (4) is 4 - 6 mm.
[0017] The present invention also provides the split film fibers prepared by the above preparation method.
[0018] The present invention also provides the application of the split film fibers in the preparation of degradable antibacterial fishing nets.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] 1. The present invention discloses a preparation method of a degradable antibacterial starch-based split film fiber based on montmorillonite-guanidine salt composite modification. By means of material compounding, problems such as insufficient antibacterial property, poor mechanical properties and ghost fishing of traditional fishing materials are solved. Plasticized starch and PBAT are selected for compounding, and by adding epoxy-based vegetable oil as a cross-linking agent, the compatibility of the two can be effectively improved, so that the prepared material has good mechanical properties. After mixing MMT with an antibacterial agent and adding it to starch and then mixing with PBAT, granulation is carried out by melt extrusion process. After the pellets are extruded and blown into a film, an antibacterial starch-based split film fiber for degradable fishing nets can be prepared.
[0021] 2. The present invention realizes the synergistic optimization of material structure and function by compounding guanidine salt polymer with montmorillonite. As a cationic polymer, PHMG can be inserted into the interlayer of montmorillonite through ion exchange, which can regulate the interlayer spacing of montmorillonite and improve the dispersion of montmorillonite in the matrix. This operation can achieve interlayer spacing regulation and dispersion strengthening. In addition, the guanidine salt polymer is adsorbed on the microbial cell membrane through electrostatic action, destroying its metabolic activity and achieving antibacterial effect, which can effectively reduce fishing gear pollution.
[0022] 3. The present invention uses materials in a specific ratio as the raw materials for blown film. After extrusion at a specific temperature, time and rotation speed, split film fibers with degradable and antibacterial functions are obtained, ensuring the smooth blown film production of starch-based split film fibers containing guanidine salt polymer and montmorillonite, and greatly improving the fluidity, processability and antibacterial property of the blown film raw materials.
[0023] 4. The present invention adds a certain proportion of guanidine salt polymer to the raw materials to endow it with antibacterial property; by adding epoxy-based vegetable oil, the present invention constructs a micro-crosslinked structure, thus achieving a long-term and effective antibacterial effect; by adding starch and PBAT to the raw materials, the gloss, processability and extrusion quality of the composite material are improved, and the softness and appearance quality of the starch-based split film fiber are greatly improved.
[0024] 5. The present invention realizes the balance between processing performance and mechanical strength by optimizing the ratio of starch-based split film fiber. First, the ratio of starch / glycerol is optimized, and the optimal mass ratio of starch to glycerol is determined to be 10:3. Secondly, the proportion of PBAT is optimized, and it is determined that PBAT accounts for 30% - 50% of the total mass. Among them, glycerol is used as a plasticizer, and under this ratio, the material can have good mechanical properties in the case of continuous blown film.
[0025] 6. The present invention realizes the continuous production of high-performance thin film materials. By optimizing the temperature of twin-screw extrusion and film blowing, a film with uniform thickness can be continuously prepared. The present invention ensures the regularity of the film, reduces the coefficient of variation of the product, and improves the quality of the product. Compared with the traditional method of single-filament processing, the preparation method of the present invention can simplify the process flow, reduce the use of equipment, lower the cost and production energy consumption, meeting the current policy requirements of energy conservation and emission reduction. In addition, the preparation process also has high production efficiency. In summary, through the composite modification of montmorillonite-guanidine salt polymer, the optimization of the starch-based material ratio, and the innovation of the film blowing process, the present invention prepares an antibacterial starch-based split film fiber for degradable fishing nets. The preparation method has significant economic benefits and ecological value in the fishing field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0027] Figure 1 Sample diagrams of the film prepared in Example 1, the film prepared in Comparative Example 1, and the split film fiber prepared in Example 1, where A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, and C is the split film fiber prepared in Example 1;
[0028] Figure 2 Infrared spectra of montmorillonite, the film prepared in Example 1, and the films prepared in Comparative Examples 1-3;
[0029] Figure 3 Diagrams for measuring the tensile strength of the film prepared in Example 1 and the films prepared in Comparative Examples 1-3;
[0030] Figure 4 Diagrams showing the antibacterial properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1-3 against Escherichia coli, where A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, C is the film prepared in Comparative Example 2, and D is the film prepared in Comparative Example 3;
[0031] Figure 5 Diagrams showing the antibacterial properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1-3 against Staphylococcus aureus, where A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, C is the film prepared in Comparative Example 2, and D is the film prepared in Comparative Example 3. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0032] The various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation on the present invention, but rather as a more detailed description of certain aspects, features, and implementation manners of the present invention.
[0033] It should be understood that the terms used in the present invention are only for describing particular embodiments and are not intended to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.
[0035] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific embodiments of the present invention specification, which are obvious to those skilled in the art. Other embodiments obtained from the specification of the present invention are obvious to those skilled in the art. The specification and examples of the present invention are merely exemplary.
[0036] Regarding the use of "comprising", "including", "having", "containing", etc. in this article, they are all open-ended terms, meaning including but not limited to.
[0037] Sources of materials and equipment used in the present invention: Montmorillonite was purchased from Sigma-Aldrich Trading Co., Ltd. (Shanghai, China); Polyhexamethylene guanidine hydrochloride was purchased from Jiangsu Chengtong Biotechnology Co., Ltd. (China); Polybutylene adipate / terephthalate was purchased from Jinhui Zhaolong (Shanxi, China); Corn starch was purchased from Yuanye Biotechnology Co., Ltd. (Shanghai, China); Epoxidized soybean oil was purchased from Macklin Biochemical Technology Co., Ltd. (Shanghai, China); Castor oil was purchased from Macklin Biochemical Technology Co., Ltd. (Shanghai, China); Palm oil was purchased from Macklin Biochemical Technology Co., Ltd. (Shanghai, China); Glycerol was purchased from Macklin Biochemical Technology Co., Ltd. (Shanghai, China); The high-speed mixer model is 8L, commercial 1800 watts, purchased from the brand Hanjiaousi on JD.com; The twin-screw extruder model is Rheomex PTW16, purchased from Thermo Fisher Scientific (USA); The granulator model is AKPL-100 type cold pelletizer, purchased from Nanjing Keya Chemical Complete Equipment Co., Ltd. (China); The blown film machine model is CSJ-5, purchased from Shanghai Changkai Electromechanical Technology Co., Ltd. (China); The winding machine model is Feiyue brand NZ-1.
[0038] Example 1
[0039] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;
[0040] (2) Corn starch was dried at 70 °C for 6 h (starch has good water absorption, and pre-drying treatment can remove excess water). The dried starch, glycerol, epoxidized soybean oil and the preliminary mixture were mixed using a high-speed mixer (each mixing time was 5 min, and a total of 5 times of mixing were carried out), and then polybutylene adipate / terephthalate was added to obtain a pre-mixture. The mass ratio of the dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The addition amount of montmorillonite was calculated according to 0.3% of the mass of the pre-mixture, the addition amount of polyhexamethylene guanidine hydrochloride was calculated according to 1% of the mass of the pre-mixture, and the addition amount of polybutylene adipate / terephthalate was calculated according to 50% of the mass of the pre-mixture;
[0041] (3) The pre-mixture was heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder was set at 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder was 120 rpm; Granulation was carried out in a granulator, and the pelletizing speed was 180 rpm to obtain pellets;
[0042] (4) The pellets were blown into a film in a blown film machine. The working temperature of the blown film machine was set at 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C. The rotation speed of the blown film machine was 80 rpm, and the traction speed of the blown film machine was 3 to obtain a film (such as Figure 1In A), it is divided and processed according to a width of 5 mm to obtain split film fibers (such as Figure 1 In C);
[0043] (5) Use a winding machine to twist the split film fibers into threads, with a twist number of 50.
[0044] Example 2
[0045] (1) Mix montmorillonite and polyhexamethylene guanidine hydrochloride to obtain a preliminary mixture;
[0046] (2) Dry corn starch at 60 °C for 7 h. The dried starch, glycerol, castor oil, and the preliminary mixture are mixed using a high-speed mixer (each mixing time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and castor oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 30% of the mass of the premix;
[0047] (3) The premix is heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder is set at 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 100 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing cutting speed is 180 rpm to obtain pellets;
[0048] (4) The pellets are blown into a film in a film blowing machine. The working temperature of the film blowing machine is set at 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C. The rotation speed of the film blowing machine is 60 rpm, and the traction speed of the film blowing machine is 3 to obtain a film. It is divided and processed according to a width of 4 mm to obtain split film fibers;
[0049] (5) Use a winding machine to twist the split film fibers into threads, with a twist number of 50.
[0050] Example 3
[0051] (1) Mix montmorillonite and polyhexamethylene guanidine hydrochloride to obtain a preliminary mixture;
[0052] (2) Corn starch is dried at 80 °C for 5 h. The dried starch, glycerol, palm oil, and the premix are mixed using a high-speed mixer (with a mixing time of 5 min each time, for a total of 5 times), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and palm oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 40% of the mass of the premix;
[0053] (3) The premix is heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set at 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 140 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain pellets;
[0054] (4) The pellets are blown into a film in a film blowing machine. The operating temperature of the film blowing machine is set at 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C. The rotational speed of the film blowing machine is 100 rpm, and the traction speed of the film blowing machine is 3 to obtain a film, which is divided and processed according to a width of 6 mm to obtain split film fibers;
[0055] (5) Use a winding machine to twist the split film fibers into a thread, with the number of twists being 50.
[0056] Comparative Example 1
[0057] (1) Corn starch is dried at 70 °C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and polyhexamethylene guanidine hydrochloride are mixed using a high-speed mixer (with a mixing time of 5 min each time, for a total of 5 times), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0058] (2) The premix is heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set at 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain pellets;
[0059] (3) Granules are blown into films in a film blowing machine. The operating temperature of the film blowing machine is set at 130°C, 140°C, 145°C, 145°C, 140°C, and 130°C. The rotational speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3, obtaining a film (such as Figure 1 in B). It is divided and processed according to a width of 5 mm to obtain split film fibers.
[0060] Comparative Example 2
[0061] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a preliminary mixture;
[0062] (2) Corn starch is dried at 70°C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and the preliminary mixture are mixed using a high-speed mixer (each mixing time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.5% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0063] (3) The premix is heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set at 130°C, 130°C, 140°C, 140°C, 145°C, 145°C, 145°C, 140°C, 130°C, and 130°C. The screw rotational speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain granules;
[0064] (4) The granules are blown into films in a film blowing machine. The operating temperature of the film blowing machine is set at 130°C, 140°C, 145°C, 145°C, 140°C, and 130°C. The rotational speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3, obtaining a film, which is divided and processed according to a width of 5 mm to obtain split film fibers.
[0065] Comparative Example 3
[0066] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a preliminary mixture;
[0067] (2) Corn starch is dried at 70 °C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and the premix are mixed using a high-speed mixer (mixing time for each time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 1% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0068] (3) The premix is heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder is set as 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain pellets;
[0069] (4) The pellets are blown into films in a film blowing machine. The working temperature of the film blowing machine is set as 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C. The rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3 to obtain films, which are divided and processed according to a width of 5 mm to obtain split film fibers.
[0070] Comparative Example 4
[0071] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a premix;
[0072] (2) Corn starch is dried at 70 °C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and the premix are mixed using a high-speed mixer (mixing time for each time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0073] (3) The premix is heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder is set as 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain pellets;
[0074] (4) Granules are blown into films in a film blowing machine. The operating temperature of the film blowing machine is set at 130°C, 140°C, 145°C, 145°C, 140°C, and 130°C. The rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3. A film is obtained and divided into strips with a width of 1 cm to obtain split film fibers.
[0075] Comparative Example 5
[0076] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a preliminary mixture;
[0077] (2) Corn starch is dried at 70°C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and the preliminary mixture are mixed using a high-speed mixer (each mixing time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0078] (3) The premix is heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set at 130°C, 130°C, 140°C, 140°C, 145°C, 145°C, 145°C, 140°C, 130°C, and 130°C. The screw rotation speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain granules;
[0079] (4) Granules are blown into films in a film blowing machine. The operating temperature of the film blowing machine is set at 130°C, 140°C, 145°C, 145°C, 140°C, and 130°C. The rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3. A film is obtained and divided into strips with a width of 2 cm to obtain split film fibers.
[0080] Comparative Example 6
[0081] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a preliminary mixture;
[0082] (2) Corn starch is dried at 70°C for 6 h. The dried starch, glycerol, epoxidized soybean oil, and the preliminary mixture are mixed using a high-speed mixer (each mixing time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0083] (3) The premix is heated and plasticized in a twin-screw extruder. The operating temperatures of the twin-screw extruder are set as 130°C, 130°C, 140°C, 140°C, 145°C, 145°C, 145°C, 140°C, 130°C, 130°C, and the screw speed of the twin-screw extruder is 120 rpm. Pelletizing is carried out in a pelletizer, and the pelletizing cutting speed is 180 rpm to obtain pellet material.
[0084] (4) The pellet material is blown into a film in a film blowing machine. The operating temperatures of the film blowing machine are set as 130°C, 140°C, 145°C, 145°C, 140°C, 130°C, the rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3 to obtain a film, which is divided and processed according to a width of 3 cm to obtain split film fibers.
[0085] Comparative Example 7
[0086] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride are mixed to obtain a preliminary mixture.
[0087] (2) Corn starch is dried at 70°C for 6 h. The dried starch, glycerol, epoxidized soybean oil and the preliminary mixture are mixed using a high-speed mixer (each mixing time is 5 min, and a total of 5 times of mixing are carried out), and then polybutylene adipate / terephthalate is added to obtain a premix. The mass ratio of the dried starch, glycerol and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix.
[0088] (3) The premix is heated and plasticized in a twin-screw extruder. The operating temperatures of the twin-screw extruder are set as 130°C, 130°C, 140°C, 140°C, 145°C, 145°C, 145°C, 140°C, 130°C, 130°C, and the screw speed of the twin-screw extruder is 120 rpm. Pelletizing is carried out in a pelletizer, and the pelletizing cutting speed is 180 rpm to obtain pellet material.
[0089] (4) The pellet material is blown into a film in a film blowing machine. The operating temperatures of the film blowing machine are set as 130°C, 140°C, 145°C, 145°C, 140°C, 130°C, the rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3 to obtain a film, which is divided and processed according to a width of 5 mm to obtain split film fibers.
[0090] (5) The split film fibers are twisted into a thread using a winding machine, and the number of twists is 100.
[0091] Comparative Example 8
[0092] (1) Mix montmorillonite with polyhexamethylene guanidine hydrochloride to obtain a preliminary mixture;
[0093] (2) Dry corn starch at 70 °C for 6 h. Mix the dried starch, glycerol, epoxidized soybean oil, and the preliminary mixture using a high-speed mixer (mixing time for each time is 5 min, and mix 5 times in total), then add polybutylene adipate / terephthalate to obtain a premix. The mass ratio of the dried starch, glycerol, and epoxidized soybean oil is 10:3:0.5. The addition amount of montmorillonite is calculated according to 0.3% of the mass of the premix, the addition amount of polyhexamethylene guanidine hydrochloride is calculated according to 1% of the mass of the premix, and the addition amount of polybutylene adipate / terephthalate is calculated according to 50% of the mass of the premix;
[0094] (3) Plasticize the premix in a twin-screw extruder. The working temperature of the twin-screw extruder is set at 130 °C, 130 °C, 140 °C, 140 °C, 145 °C, 145 °C, 145 °C, 140 °C, 130 °C, 130 °C. The screw speed of the twin-screw extruder is 120 rpm; Pelletizing is carried out in a pelletizer, and the pelletizing speed is 180 rpm to obtain pellets;
[0095] (4) Blow the pellets into a film in a film blowing machine. The working temperature of the film blowing machine is set at 130 °C, 140 °C, 145 °C, 145 °C, 140 °C, 130 °C. The rotation speed of the film blowing machine is 80 rpm, and the traction speed of the film blowing machine is 3 to obtain a film. Cut and process it according to a width of 5 mm to obtain split film fibers;
[0096] (5) Use a winding machine to twist the split film fibers into a thread, and the number of twists is 200.
[0097] Experimental Example 1
[0098] Measure the infrared spectra of montmorillonite, the film prepared in Example 1, and the films prepared in Comparative Examples 1 to 3. Measure the mechanical properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1 to 3. Measure the antibacterial properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1 to 3.
[0099] As Figure 2 shown, they are the infrared spectra of montmorillonite, the film prepared in Example 1, and the films prepared in Comparative Examples 1 to 3. The characteristic peak at 3200 - 3300 cm -1 is the hydroxyl peak of the interlayer water in montmorillonite. It can be seen from Figure 2 that after adding montmorillonite to the starch-based material in Example 1, Comparative Example 2, and Comparative Example 3, the characteristic peak of the hydroxyl group shifts towards the high wavenumber direction. This is because there is an interaction between polyhexamethylene guanidine hydrochloride and montmorillonite in the system, which affects the layer spacing and causes the characteristic peak of the interlayer water to shift.
[0100] As Figure 3 shown, it is the mechanical property diagram of the film prepared in Example 1 and the films prepared in Comparative Examples 1 to 3. It can be seen from Figure 3 that when the montmorillonite addition amount shown in Example 1 is 0.3 wt%, the tensile property is the best. However, as the montmorillonite addition content increases (Comparative Examples 2 and 3), the mechanical properties decline. This is because montmorillonite generates interactions in the matrix, thereby realizing effective load transfer. As the montmorillonite content increases, it agglomerates in the matrix and the dispersibility becomes poor, resulting in the decline of properties.
[0101] As Figure 4 and Figure 5 shown, it is the antibacterial property diagram of the film prepared in Example 1 and the prepared film. It can be seen from Figure 4 and Figure 5 that the films prepared in Example 1 and Comparative Examples 1 to 3 have inhibitory effects on Escherichia coli and Staphylococcus aureus, and the inhibitory effect on Staphylococcus aureus is more obvious. This may be because the cell wall structure of Staphylococcus aureus is relatively simple, and guanidine salt polymers can more easily bind to the teichoic acid and peptidoglycan on the cell wall surface, destroying the integrity of the cell wall, thereby causing the death of bacteria. The outer membrane structure of Escherichia coli can effectively prevent the adsorption and penetration of montmorillonite, making its antibacterial effect relatively weak. Therefore, the antibacterial property can reduce the biological contamination of the material.
[0102] Measure the mechanical properties of the split film fibers prepared in Example 1 and the split film fibers prepared in Comparative Examples 4 to 6.
[0103] Table 1 Mechanical properties of the split film fibers prepared in Example 1 and Comparative Examples 4 to 6
[0104] Group Tensile strength (MPa) Young's modulus (MPa) Example 1 9.19 112.44 Comparative Example 4 7.46 83.85 Comparative Example 5 6.49 77.33 Comparative Example 6 5.36 69.83
[0105] According to the records in Table 1, it can be known that the split film fibers have good mechanical properties when the width is 5 mm and the width is relatively small (Example 1).
[0106] Measure the mechanical properties of the threads prepared in Example 1 and the threads prepared in Comparative Examples 7 and 8.
[0107] Table 2 Mechanical properties of the threads prepared in Example 1, Comparative Example 7 and Comparative Example 8
[0108] Group Breaking strength (N) Elongation at break (%) Example 1 3.61 695.45 Comparative Example 7 3.21 662.83 Comparative Example 8 3.31 699.51
[0109] As can be seen from Table 2, the effect of twisting on the mechanical properties of split film fibers is small because the twist used is close to or lower than the value that can affect the properties, resulting in no obvious effect on the internal interface structure of the split film fibers, and thus the mechanical properties do not change significantly macroscopically.
[0110] The embodiments described above are only descriptions of the preferred embodiments of the present invention and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations and improvements made by those of ordinary skill in the art to the technical solutions of the present invention shall fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing antibacterial starch-based split film fibers for degradable fishing nets, characterized in that: The following steps are involved: (1) mixing the layered nanomaterial with the guanidine polymer to obtain a primary mixture; (2) drying the starch, mixing the dried starch, glycerol, epoxy vegetable oil and the primary mixture obtained in step (1), and then adding polybutylene adipate / terephthalate to obtain a premix; (3) heating and plasticizing the premix obtained in step (2), and granulating to obtain pellets; (4) The pellets obtained in step (3) are blown into a film to obtain a thin film, which is then split to obtain split film fibers.
2. The preparation method according to claim 1, characterized in that: The layered nanomaterial in step (1) is montmorillonite; the guanidine salt polymer in step (1) is polyhexamethyleneguanidine hydrochloride.
3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 60-80° C., and the drying time is 5-7 hours.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the dried starch, glycerol and epoxy vegetable oil in step (2) is 10:3:0.5; the mass of the layered nanomaterial in step (1) accounts for 0.3% of the mass of the premix; the mass of the guanidine polymer in step (1) accounts for 1% of the mass of the premix; and the mass of the poly(butylene adipate) / terephthalate) in step (2) accounts for 30% to 50% of the mass of the premix.
5. The preparation method according to claim 1, characterized in that: The starch in step (2) is corn starch; the epoxy vegetable oil in step (2) is one of epoxy soybean oil, castor oil and palm oil.
6. The preparation method according to claim 1, characterized in that: The heating and plasticizing in step (3) is carried out in a twin-screw extruder, and the operating temperature of the twin-screw extruder is set at 130°C, 130°C, 140°C, 140°C, 145°C, 145°C, 140°C, 130°C, and 130°C, and the screw speed of the twin-screw extruder is 100-140rpm.
7. The preparation method according to claim 1, characterized in that: The pelletizing speed of the granulation in step (3) is 180 rpm.
8. The preparation method according to claim 1, characterized in that: The film blowing described in step (4) is carried out in a film blowing machine, and the working temperature of the film blowing machine is set according to 130°C, 140°C, 145°C, 145°C, 140°C, and 130°C, the rotation speed of the film blowing machine is 60-100rpm, and the traction speed of the film blowing machine is 3; the width of the segmentation processing described in step (4) is 4-6mm.
9. The split film fiber prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the split film fiber as claimed in claim 9 in the preparation of degradable and antibacterial fishing nets.
Citation Information
Patent Citations
Preparation method, product and application of nano-montmorillonite reinforced starch-based biodegradable film blowing material
CN112405931A
Long-acting antibacterial degradable polyester food packaging film and preparation method thereof
CN114907676A
Degradable meal box and preparation method thereof
CN118756522A
Process for the manufacture of a lignocellulosic fibre-based composite material using carbohydrate-based pellets and composite material obtained by such process
WO2023006847A1